This must be the place (to commit a crime).: testing the law of crime concentration in Milan, Italy - Favarin, Serena (European journal of criminology, 2018)
The dense distribution of crime in a small number of micro places led to the formulation of a law of crime concentration applicable across cities and stable over time. This law has rarely been tested in Europe and has never been tested in Italy. In addition, there is a lack of extensive knowledge about its determinants. Therefore, the main objectives of this study are to test the presence and the stability of crime concentration in a different urban context and to explain this concentration. A street segment analysis and a group-based trajectory analysis were conducted to test the presence and the stability of crime concentration in the city of Milan (Italy), and negative binomial regression models were run to understand the main determinants of this concentration. The findings confirm the presence of crime concentration at street segment level, but only a few segments can be considered to be highly criminogenic over time. Social disorganization factors play an important role in explaining crime concentration, even though opportunity factors also coincide in this explanation. Despite their differences, cities around the world share the same crime concentration. The generalization of these findings is an important step in the development of common knowledge. Nevertheless, in Milan only a few segments are chronic hot spots. The stability pattern in the city needs to be further analysed using different methods. A theoretical integration approach considering both situational and social disorganization factors is promising in understanding why crime occurs in urban areas.